Innovative Instructional Strategies for The Digital Age: A ‎Study on Multimedia-Enhanced Writing Pedagogy In English ‎Language Classrooms - Sivakami , N.; Gunasekaran , Dr. S. (International Journal of Basic and Applied Sciences, 2025)
In the digital age, using multimedia tools—such as videos, audio clips, visual organizers, and ‎collaborative writing platforms—has changed how writing is taught in English classrooms. ‎These tools make lessons more engaging, interactive, and accessible to diverse learners. This ‎study examines how these multimedia-supported strategies help improve undergraduate ‎students’ writing skills in Tamil Nadu’s engineering colleges. The research uses both test results ‎and classroom feedback to assess the impact. Students who learned through multimedia tools ‎showed clear improvements in vocabulary, sentence structure, idea generation, and overall ‎writing coherence. They were also more motivated, involved, and confident in their learning. ‎The study highlights key challenges such as uneven access to digital tools, the need for teacher ‎training, and effective use of available resources. It concludes by recommending that ‎technology be used not just as an optional aid but as a key part of lesson planning, teaching, ‎and evaluation. This study shows how multimedia can improve both writing quality and student ‎participation in English language education, while calling for continuous teacher development ‎to keep up with digital tools and methods.